Overcoming Anxiety in Chronic Kidney Failure Patients Undergoing Hemodialysis with Finger Relaxation Therapy and Lemon - Arnanditya, Rezza Hafidh; Dewi, Apri Rahma; Pujiarto, Pujiarto (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Chronic renal failure is a decrease in kidney function characterized by a decrease in the glomerular filtration rate (less than 60 mL/min). Anxiety is a common symptom in patients with chronic renal failure undergoing hemodialysis, which can affect the quality of the patient both physically and psychologically. The finger-holding relaxation technique is a simple relaxation technique related to the fingers and the flow of energy in the body. Lemon aromatherapy is a type of aromatherapy that contains chemical compounds that have antidepressant properties, as well as mild sedatives. This research aims to determine and analyze nursing care for patients with chronic renal failure undergoing hemodialysis with anxiety nursing problems before and after using the finger-holding relaxation technique and lemon aromatherapy. The research design used is an applied research design. The subjects in this study were 18 respondents who were in accordance with the results of the HARS scale questionnaire measurements. The intervention was carried out twice, before and one hour after the patient underwent hemodialysis for 15 minutes. The results of the study before the application of finger-holding relaxation therapy and lemon aromatherapy in the hemodialysis room on 18 respondents showed the results of 6 respondents with severe anxiety (33.3%), 8 respondents with moderate anxiety (44.5%) and 4 respondents with mild anxiety (22.2%). The results of the study after the application of finger-holding relaxation therapy and lemon aromatherapy in the hemodialysis room showed the results of a score of 5 respondents with moderate anxiety (27.7%), 9 respondents with mild anxiety (50%), 4 no anxiety (22.3%). The conclusion of this study is that finger-holding relaxation therapy and lemon aromatherapy have been proven to reduce anxiety levels because the benefits of finger-holding relaxation therapy and lemon aromatherapy are in line with aspects that can affect anxiety.